Radiographic Evidence of Early Posttraumatic Osteoarthritis following Tibial Plateau Fracture Is Associated with Poorer Function - Maseda, Meghan; Perskin, Cody R.; Konda, Sanjit R.; Leucht, Philipp; Ganta, Abishek; Egol, Kenneth A. (The Journal of Knee Surgery, 2022)
To determine if radiographic evidence of posttraumatic osteoarthritis (PTOA) following tibial plateau fracture correlates with poorer clinical and functional outcomes, patients with tibial plateau fractures were followed at 3, 6, and 12 months. All patients had baseline radiographs and computed tomography scan. Radiographs obtained at each follow-up were reviewed for healing, articular incongruence, hardware positional changes, and the development of postinjury arthritic change. Cohorts were determined based on the presence (PTOA) or absence (NPTOA) of radiographic evidence of PTOA. Demographics, fracture classification, complications, additional procedures, and functional status were compared between cohorts. Sixty patients had radiographic evidence of PTOA on follow-up radiographs at a mean final follow-up of 24.2 months. The NPTOA cohort was composed of 210 patients who were matched to the PTOA cohort based on age and Charlson comorbidity index. Mean time to fracture union for the overall cohort was 4.86 months. Cohorts did not differ in Schatzker classification, time to healing, injury mechanism, or baseline Short Musculoskeletal Function Assessment (SMFA). Patients with PTOA had a greater degree of initial depression and postoperative step-off, higher incidence of initial external fixator usage, higher rates of reoperation for any reason, and higher rates of wound complications. Associated soft tissue injury and meniscal repair did not coincide with the development of PTOA. Range of motion and SMFA scores were significantly worse at all time points in patients with PTOA. Although fracture patterns are similar, patients who required an initial external fixator, had a greater degree of initial depression or residual articular incongruity, underwent more procedures, and developed an infection were found to have increased incidence of PTOA. Radiographic evidence of osteoarthritis correlated with worse functional status in patients. The goal of surgery should be restoration of articular congruity and stability to mitigate the risk of PTOA, although this alone may not prevent degenerative changes. Patients with early loss of range of motion should be aggressively treated as this may precede the development of PTOA.
Keywords: osteoarthritis; posttraumatic arthritis; tibial plateau; PTOA